Lower Urinary Tract Symptoms, Benign Prostatic Hyperplasia, Erectile Dysfunction, and Phosphodiesterase-5 Inhibitors - Roehrborn, Claus G (MedReviews, LLC, 2004)
Many patients who present to their healthcare provider with lower urinary tract symptoms (LUTS) due to benign prostatic hyperplasia (BPH) will also have erectile dysfunction (ED), and vice versa. Although α-adrenergic receptor blockers and 5-α-reductase inhibitors are highly effective in treating BPH-associated LUTS, these agents have sexual adverse effects that cause many men to discontinue therapy. The discovery of nitric oxide as a major factor in the mechanism of erection has led to the development of new drugs for ED, including the phosphodiesterase (PDE) inhibitors. Preliminary data support the theory that inhibition of PDE isoenzymes in the prostate may improve LUTS due to BPH through relaxation of prostatic smooth muscle. Further studies of PDE inhibitors in men with ED and BPH-associated LUTS are indicated.